Sugar-sweetened and diet beverage consumption is associated with cardiovascular risk factor profile in youth with type 1 diabetes - Bortsov, Andrey V. (Acta Diabetol, 2011)
The prevalence of cardiovascular disease (CVD) risk factors among youth with type 1 diabetes is high and associated with age, gender, and race/ethnicity. It has also been shown that youth with type 1 diabetes often do not follow dietary recommendations. The objective of this cross-sectional observational study was to explore the association of sugar-sweetened and diet beverage intake with A1c, plasma lipids, adiponectin, leptin, systolic, and diastolic blood pressure in youth with type 1 diabetes. We examined data from 1,806 youth age 10–22 years with type 1 diabetes, of which 22% were minority (10% Hispanic, 8% African Americans, 4% other races) and 48% were female. Sugar-sweetened beverage, diet beverage, and mineral water intake was assessed with a food frequency questionnaire. After adjustment for socio-demographic and clinical covariates, physical activity and total energy intake, high sugar-sweetened beverage intake (at least one serving per day vs. none), was associated with higher levels of total cholesterol, LDL cholesterol, and plasma triglycerides, but not with A1c. High diet beverage intake was associated with higher A1c, total cholesterol, LDL cholesterol, and triglycerides. These associations were partially confounded by body mass index, saturated fat and total fiber intake. High sugar-sweetened beverage intake may have an adverse effect on CVD risk in youth with type 1 diabetes. Diet beverage intake may be a marker of unhealthy lifestyle which, in turn, is associated with worse metabolic control and CVD risk profile in these youth. Youth with diabetes should be encouraged to minimize sugar-sweetened beverage intake.